The Global Cross-Laminated Timber (CLT) Industry: A Systematic Review and a Sectoral Survey of Its Main Developers - De Araujo, Victor [UNESP]; Christoforo, André (MDPI, 2023)
Recently, both authors led a comprehensive review to discuss cross-laminated timber (CLT) as an engineered wood product, addressing the information and discussion on this building input in terms of the main details, materials, production forms, performances, codes, sustainability, applications, and perspectives for residential uses. The current scenario of CLT developers was raised in that previous paper as one of the missing factors in the available literature, and was the reason why this gap became the main goal of the present study. A global perspective was driven to provide information and discussion to every possible stakeholder. A systematic review on this sector was carried out, through the Web of Science and Scopus databases, to collect information and confirm this gap, using a representative method. CLT manufacturers were identified by their own websites, using a blended strategy formed by the systematic review results combined with the search for these companies using the Google search engine. Nearly a hundred CLT developers were identified and analyzed, in a representative sampling process. Results demonstrated that the CLT industry has manufacturing plants on the five habitable continents, which evinced a global commercial interest in this timber forest product. Despite the global presence of this mass timber product, most producers are concentrated in the northern hemisphere, despite being willing to serve international markets.
Keywords: building materials; sectoral survey; timber buildings; wood industry; wood products